2012
DOI: 10.1016/j.apgeochem.2011.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic accumulation and speciation in plants from different habitats

Abstract: Understanding As accumulation in plants is necessary in order to alleviate problems with As in the environment and to improve sustainable As phytotechnologies. To find suitable candidates for phytoremediation purposes and to investigate specific accumulation patterns due to growth habitat and plant groups, As accumulation in 124 plant species collected from different habitats and speciation in 6 of these plant species, was determined. The data show that submerged plants have a higher accumulation than emergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 27 publications
1
21
0
2
Order By: Relevance
“…However, it does not cover all species analyzed in scientific studies, quantifying only the species As III, As V, Monomethyl Arsenic (MMA), Dimethyl Arsenic (DMA) and Arsenic Betaine (AsB). Species such as trimethylarsine oxide (TMAO) found in plants (Bergqvist and Greger, 2012) or Arsenocoline (AsC) found in marine animals (Raber et al 2012), are not accredited by any Brazilian laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…However, it does not cover all species analyzed in scientific studies, quantifying only the species As III, As V, Monomethyl Arsenic (MMA), Dimethyl Arsenic (DMA) and Arsenic Betaine (AsB). Species such as trimethylarsine oxide (TMAO) found in plants (Bergqvist and Greger, 2012) or Arsenocoline (AsC) found in marine animals (Raber et al 2012), are not accredited by any Brazilian laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…Demir hidrit ve Fe, Mn, Al oksit/hidroksitlerin çözünürlüğü pH'a bağlı olarak değiştiğinden, arsenitin çözünürlüğü pH düştükçe artarken, arsenatın çözünürlüğü artan pH ile artmaktadır [5].…”
Section: Arsenik Bileşikleri Ve Toksik Etkileriunclassified
“…Ayrıca taze ve pişmiş olarak insanlar tarafından doğrudan tüketilen, domates, soğan, patates gibi tarımsal ürünlerde As kirlenmesi araştırmaları olmasına rağmen genel olarak çalışmalar, toprakta As kirliğinin etkisi ile ilgilidir. Çalışma sonuçlarında pirinç gibi tarım ürünlerinin çok fazla tüketimi ile insanların yüksek miktarda As alımına neden olabileceği açıklanmıştır [5], [6].…”
Section: Introductionunclassified
“…Analyses of a range of plant species with the aid of analytical techniques such as HPLC/ICPMS/ES-MS and synchrotron radiation-based X-ray absorption spectroscopy (XAS) have shown that both terrestrial and freshwater aquatic plants contain predominantly inorganic As [26][27][28] but their relative proportions vary among the plant species. Analyses of a range of plant species with the aid of analytical techniques such as HPLC/ICPMS/ES-MS and synchrotron radiation-based X-ray absorption spectroscopy (XAS) have shown that both terrestrial and freshwater aquatic plants contain predominantly inorganic As [26][27][28] but their relative proportions vary among the plant species.…”
Section: Arsenic Speciation and Mobilizationmentioning
confidence: 99%
“…As is present predominantly as trivalent species [As(III)] [29][30][31][32] and is the main species in the fronds of As-hyperaccumulating ferns [29,33,34]. Many plant species also contain small amounts of methylated As compounds, such as MMA, DMA, TMAO, and, occasionally, the tetramethylarsonium ion [26][27][28]. However, As hyperaccumulators such as Pteris vittata and Pteris cretica appear to be exceptions, containing arsenite mostly as uncomplexed species, due to low phytochelatin (PC) concentrations in tissues [35,36].…”
Section: Arsenic Speciation and Mobilizationmentioning
confidence: 99%